Panama : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Panama's economic performance is expected to remain strong. Real GDP slowed to 6.2 percent in 2014, reflecting a slower pace of public investment, continued weakness in Colon Free Zone activity, and delays in the Canal expansion. Growth is expected to remain stable in 2015. Lower oil prices and the U.S. recovery will be positive forces but these factors will be offset by U.S. dollar appreciation and some lags in new public investment. Over the medium term, the expanded Canal and the new copper mine should help maintain growth at 6-7 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet